Techno-economic analysis of renewable hybrid system microgrids for minimizing grid power outages in residential areas - Marzieh Salehi; Majid Khanali; Hassan Ghasemi-Mobtaker (Cleaner Engineering and Technology)
The increasing frequency of grid blackouts and CO2 emissions in countries heavily reliant on fossil fuels for their national power grids, such as Iran, has led to reduced power supply reliability and environmental challenges. Effectively utilizing renewable energy to address blackouts is challenging for governments due to the intermittent nature of renewables, peak demand variations, and potential excess generation. Therefore, this study examines the techno-economic feasibility of a hybrid renewable microgrid to mitigate power outages in large-scale residential areas under various outage scenarios. Real demand and capacity shortage data were imported into HOMER software to optimize the grid-connected system using a cycle charging dispatch strategy. Different scenarios were considered, including outages based on existing conditions, during renewable resource peaks, and during demand peaks. Results show that if the government schedules outages during sunny hours to compensate for capacity shortages using photovoltaics, large-scale renewables become more cost-effective. The optimal solution supplies more than 45% of the 591 MW h/day demand with renewables by installing 49.8 MW of PV, 22.5 MW of wind turbines, a 34.5 MW h battery bank, and a 5 MW electrolyzer plant. This solution results in an energy cost of $0.07/kWh and less than 7.7% excess electricity, improving the annual capacity shortage to less than 1% of demand. Additionally, more than 220 tons/year of green hydrogen is produced by utilizing over 10 GW h/year of excess power, justifying the slight cost increase associated with the electrolyzer. These results highlight the success of renewables optimization to supply capacity shortages for policymakers.